Organic Farming An initiative for tribal farmers - Singh, Ajeet Kumar; Pandey, Brijesh; Rajan, Neha; Singh, Nidhi (Indian Farming, 2019)
India has traditionally been a country of organic agriculture, but the growth of modern scientific, input intensive agriculture has pushed it to wall. With the increasing awareness about the safety and quality of foods, long term sustainability of the system and accumulating evidences of being equally productive, the organic farming has emerged as an alternative system of farming which not only addresses the quality and sustainability concerns, but also ensures a debt free, profitable livelihood option for the most vulnerable section of Indian farming community particularly schedule tribes.